A Comparative Study of Subsoil Profile In Southern End of Golf Ground, Health Campus, USM, Kubang Kerian by Atomic Absorption SpectToscopy (AAS) - Mohideen, Asfarina Jamal (Universiti Sains Malaysia, 2006)
Atomic absorption spectrophotometry (AAS) is being used for analyzing various metals present in soil. This comparative study of soil profile by AAS is done to show the difference in metal ion concentrations in different soil samples, which were collected from four different points such as S 1, S2, S3 and S4 in southern side of golf ground, USM, Kubang Kerian. In each point, samples were also collected in four different depths, namely the topsoil, soil from Yz foot depth, soil from 1 foot depth, and soil from 11/2 feet depth. These 16 soil samples have been analyzed using AAS. In this study, the analysis of soil samples was done in two ways. Firstly preliminary examinations were made under stereomicroscope. Secondly the samples were examined under AAS to fmd out the different metal ion concentration present in the soil samples collected in different points and different depths. The metal ions were extracted using EDTA, because EDTA form complex with many metals to form chelate compounds. The extracted compounds were purified and run through AAS and recorded the different metal ion concentrations. The purpose of this study is to compare the metal ion concentration in soil samples collected in different points and in different depths from the southern end of golf ground. The presence of metal ions in subsoil profile were compared and recorded. To make a fruitful study, ten metals have been chosen and their concentrations present in the above 16 soil samples were studied. The chosen metals under this study include Na, K, Pb, As, Zn, Cd, Fe, Mg, Ca and Cu. The selection of the most suitable elements for forensic discrimination purposes is depending on the nature of soil under question. Also carried out a simulated crime scene soil analysis where in crime scene soil sample and soil collected from the suspected were analyzed under AAS. The result clearly indicated similar metal ions concentration present in both samples. Hence this is a better method for the forensic analysis of soil.